Different Fish Meal and Fish Oil Dietary Levels in European Sea Bass: Welfare Implications After Acute Confinement Stress - Pelusio, Nicole Francesca; Bonaldo, Alessio; Gisbert, Enric; Andree, Karl B.; Esteban, Maria Angeles; Dondi, Francesco; Sabetti, Maria Chiara; Gatta, Pier Paolo; Parma, Luca (Frontiers in Marine Science, 2022)
To provide practical feeding management guidelines preceding a stressful episode during farming practices, European sea bass juveniles (initial weight: 72.3 g) were fed for 60-days different fish meal (FM) and fish oil (FO) dietary levels [high (30% FM, 15% FO, FM30/FO15), intermediate (20% FM, 7% FO, FM20/FO7), and low (10% FM, 3% FO, FM10/FO3)] in triplicate conditions. Fish were then fasted for 36 h and exposed to a 2-h acute crowding (80 kg m–3 biomass). Plasma biochemistry, skin mucus parameters and gene expression of stress and immune-related genes were performed before, at 2 and 24 h after crowding. At the end of the trial, the FM10/FO3 group showed lower final body weight, weight gain, and specific growth rate compared to the other treatments. Most of the plasma parameters were mainly affected by crowding condition rather than diet; however, after stress, lactate was higher in the FM30/FO15 group compared to the other treatments. Similarly, protease, antiprotease, peroxidase and lysozyme in skin mucus were mostly affected by crowding conditions, while fish fed FM10/FO3 displayed higher skin mucosal IgM and bactericidal activity against Vibrio anguillarum and V. harveyi. Most of the stress-related genes considered (hsp70 and gr-1 in the brain; hsp70, gr-1 and gr-2 in the head kidney), showed an overall expression pattern that increased over time after stress, in addition, hsp70 in the head kidney was also up-regulated in fish fed FM30/FO15 after stress. Higher plasmatic lactate together with the up-regulation of some stress-related transcripts suggest a higher reactivity to acute crowding of the stress-response mechanism in fish fed high FM and FO dietary levels. Otherwise, the higher skin mucosal IgM and bactericidal activity observed in fish fed FM10/FO3 dietary levels seems to indicate that acute crowding was able to activate a higher pro-inflammatory response in this treatment. Overall, the results of the present study seem to indicate that 10% FM and 3% FO dietary levels might affect stress and immune responses.